2003
DOI: 10.1093/gerona/58.8.b687
|View full text |Cite
|
Sign up to set email alerts
|

Denervation Stimulates Apoptosis But Not Id2 Expression in Hindlimb Muscles of Aged Rats

Abstract: Inhibitors of differentiation (Id) proteins are repressors of myogenic regulatory factors and have been implicated in apoptosis and muscle atrophy during aging. Indeed, we have previously found that Id levels are elevated in muscles from old rodents, possibly as a consequence of loss of alpha-motoneurons during senescence. To determine if Id2 proteins increase after denervation and if this is accompanied by increased apoptosis in aged as compared with adult animals, the gastrocnemius and soleus muscles were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
77
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 53 publications
(79 reference statements)
13
77
0
Order By: Relevance
“…† P<0.05 indicates significant difference from aged (26 month) group. n=4 each group It has been suggested that the mechanisms of agerelated apoptosis may differ in fast-and slow-twitch muscle types [21][22][23]. The data of the present study are consistent with this notion.…”
Section: Discussionsupporting
confidence: 91%
“…† P<0.05 indicates significant difference from aged (26 month) group. n=4 each group It has been suggested that the mechanisms of agerelated apoptosis may differ in fast-and slow-twitch muscle types [21][22][23]. The data of the present study are consistent with this notion.…”
Section: Discussionsupporting
confidence: 91%
“…This pattern was analogous to that observed for tissue levels of HNE and 3-nitrotyrosine, suggesting that the enhanced oxidative and nitrosative stress might have influenced the mitochondrial content of those proteins (Savory, Rao, Huang, Letada, and Herman 1999;Mishra, Randis, Ashraf, and ivoria-Papadopoulos 2006;Qin, Yan, Patel, Liu, and Dong 2006). However, in contrast to previous studies (Alway et al 2002;Alway et al 2003;Song et al 2006;Chung and Ng 2006), we did not detect an age-related increase in the Bax to Bcl-2 ratio. While this finding may be interpreted as a compensatory action aimed at preventing myonuclei loss, we found a concomitant increase of total mitochondrial content of Bid.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to previous observation in both human [31] and rat muscles [32,33], we observed that the specific tension (maximum tetanic force per muscle per muscle mass or cross-sectional area) was decreased in the muscles from the old animals [13].…”
Section: Effects Of Ageingsupporting
confidence: 91%